Linking New Paradigms in Protein Chemistry to Reversible Membrane-Protein Interactions - Halskau, Oyvind; Muga, Arturo; Martinez, Aurora (Current Protein and Peptide Science, 2009)
Amphitrophic proteins are soluble, globular proteins that may - under certain conditions - interact reversibly with a plasma membrane. How this apparent duality in the properties of a protein is achieved has been a relatively littlestudied subject until recently. In this review we aim to summarize the current knowledge regarding some important amphitrophic systems in which the interaction with the membrane does not require post-translational functional groups, but is an intrinsic property of the protein. We discuss mechanisms and driving forces involved in membrane binding in the context of two related concepts in protein folding and function that appear to have implications for understanding the association of proteins with membranes; first, the existence of some proteins with low-energy barrier heights for protein folding. Low folding barriers and the ability of proteins to form stable molten globule states are rationales that can explain how a protein can gain access to an ensemble (or continuum) of non-native conformations that are competent membrane binders. Second, the focus on order-disorder and disorder-order transitions to explain protein function, a concept which has been mainly developed within the novel protein trinity paradigm. Here, protein function can arise from any of three thermodynamic states: a solid, crystal-like state; a dense fluid state; and an extended disordered state. Together these concepts aid to understand amphitrophic mechanism and to unify interpretations of protein behaviour with respect to the degree of (un)unfolding of the membrane-bound proteins.
Keywords: phospholipids